Pengembangan Media Pembelajaran Video Interaktif Table Manner untuk Meningkatkan Perilaku Makan bagi Disabilitas Intelektual: The Development of Interactive Video Learning Media on Table Manners to Improve Dining Behavior for Individuals with Intellectual Disabilities - Widyadhari Milenia Vanosta (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
This study aims to develop an interactive video-based learning media on table manners specifically designed to improve dining behavior among individuals with intellectual disabilities. The media is tailored to individual needs by integrating visual, auditory, and simple interactive elements suitable for the learners’ abilities. The research employs the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), which includes needs analysis, media design, prototype development, implementation with participants, and effectiveness evaluation. The trial results indicate that the interactive video effectively helps participants understand fundamental concepts of proper dining behavior, such as using utensils, appropriate seating, and table etiquette. Improvements in dining behavior were observed through pretest and posttest measurements, showing significant positive changes among participants. The media also received positive feedback from teachers and parents, who noted that the video provides an engaging and easy-to-understand learning experience for learners. Therefore, this media demonstrates potential as an inclusive and effective learning tool to support life skills development for individuals with intellectual disabilities.   ABSTRAK Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa video interaktif bertema table manner yang dirancang khusus untuk meningkatkan perilaku makan bagi penyandang disabilitas intelektual. Media ini dirancang dengan pendekatan berbasis kebutuhan individu, menggabungkan elemen visual, audio, dan interaksi sederhana yang sesuai dengan kemampuan peserta didik. Metode penelitian menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, and Evaluation) yang mencakup analisis kebutuhan, perancangan media, pengembangan prototipe, implementasi pada peserta didik, dan evaluasi efektivitas. Hasil uji coba menunjukkan bahwa video interaktif ini efektif dalam membantu peserta didik memahami konsep dasar perilaku makan yang baik, seperti penggunaan alat makan, tata cara duduk, dan etika saat makan. Peningkatan perilaku makan diamati melalui pengukuran pretest dan posttest, dengan hasil signifikan pada perubahan perilaku positif peserta didik. Media ini juga mendapatkan respons positif dari guru dan orang tua yang menilai bahwa video memberikan pengalaman belajar yang menarik dan mudah dipahami oleh peserta didik. Dengan demikian, media ini berpotensi menjadi alternatif pembelajaran yang inklusif dan efektif untuk mendukung pengembangan keterampilan hidup bagi penyandang disabilitas intelektual.